Evidence of occurring alfalfa mosaic virus in potato plants in Assam, India - Halabi, Mohamad Hussam (Virusdisease, 2019)
Alfalfa mosaic virus (AMV, family Bromoviridae, genus Alfamovirus) has an extensive host range. The reports of AMV available in India were dated far back as 1979 and 1981 found in alfalfa and brinjal crops respectively. In January 2019, field surveys were conducted for viral diseases infecting potato in Sonitpur and Jorhat districts of Assam state of India. Severe yellow mosaic or calico pattern symptom, consistent with infection with AMV were observed with an incidence of approximately 25% of the plants found in farmer’s fields. Sixty different symptomatic leaf samples including those associated with AMV observed were collected at random and were analysed to detect the presence of AMV. Leaf samples were frozen in liquid nitrogen and total RNA extracted from them were analyzed by one step polymerase chain reaction to detect the presence of AMV reported in potato inducing similar symptoms using a specific pair of primers for coat protein gene. An expected amplicon size of 351 bp was observed in 70% of the symptomatic leaf samples when the PCR products were analyzed on a 1.2% agarose gel. The PCR product for one sample each from the surveyed districts was eluted, purified and sequenced. The sequence results obtained were compared with those deposited in GenBank database. Blastn analysis of the sequenced isolates submitted to GenBank revealed nucleotides similar to AMV Iran isolate sequences. To our knowledge, this is the first report of AMV infecting potato in India.